Effect of Age, Gender, and Intake Rate on Public Health Complaint Around the Traditional Gold Mining, Kuantan Hilir District, Kuantan Singingi Regency, Riau Province - Cindhy Giovanni; Nurmaini Nurmaini; Sri Malem Indirawati (Budapest International Research and Critics University, 2022)
The research objective is to analyze effect of age, gender, and intake rate on public health complaint around the Traditional Gold Mining, Kuantan Hilir District, Kuantan Singingi Regency, Riau Province. This research is quantitative with a cross sectional research design. The population is people who use wells as a source of drinking water and are in 3 villages located on the banks of the river near the location of the Traditional Gold Mining, Kuantan Hilir District, Kuantan Singingi Regency, namely Kasang Limau Sunda Village 38 families, Teratak Jering Village 96 families, and Rawang Village Oguang 567 families with a total of 701 families. The sample in this study are people who consumed water from dug wells in the area around the Gold Mining in 3 villages in Kuantan Hilir District, namely Kasang Limau Sundai Village, Teratak Jering Village, and Rawang Oguang Village. Sampling was done by purposive sampling. After calculating the known population in the 3 villages amounted to 701 families, then obtained a sample of 84 research samples. Data analysis used multivariate analysis. The results show that age has effect on public health complaint around the Traditional Gold Mining, Kuantan Hilir District, Kuantan Singingi Regency, Riau Province. Gender and intake rate have no effect on public health complaint around the Traditional Gold Mining, Kuantan Hilir District, Kuantan Singingi Regency, Riau Province.